Composition analysis of ultrapyrolytic recycled products from various brands of ultra-heavy mining truck waste tires - Mohammadreza Sharifian; Ali Farhadian; Hamid Almasiyeh; Seyed Hadi Hoseinie (Scientific Reports)
Abstract Off-the-road (OTR) waste tires of heavy mining dump trucks have devastating environmental effects. They are also a reliable source of some valuable raw materials, which could be returned to the manufacturing process by recycling. Pyrolysis is a promising and eco-friendly approach for recycling big, heavy tires. This paper aims to use a laboratory-scale reactor to investigate the pyrolysis process and analyze the recycled pyrolytic yields of OTR ultra-heavy mining waste tires in large Iranian open pit mines. After developing the pyrolyzer set up in a laboratory, eight popular tire brands used in open-pit mine dump truck fleets were selected and collected as the sampling population. Smaller samples were prepared by cutting and downsizing them into small pieces. Each tire brand was then processed under pyrolysis conditions with operating parameters including the batch weight of 2.5 kg, the maximum temperature of 600 °C, and residence time varying from 120 to 173 min based on the specific tire brand. The percentage of the main products are fuel oil (31–36%), non-condensable gases (10–13%), carbon black (31–38%), and steel wire (18–25%). The results show that the thermochemical decomposition of OTR mining waste tire samples occurs within a temperature range of 300–400 °C, proceeding through three distinct degradation phases (oil, char, and gas). As the temperature increased, due to secondary cracking reactions in volatile matter, the oil yield fell while gas yield rose in the same order. Analysis of the produced pyrolytic oil and char suggests that both products have potential applications as fuels. Moreover, the FESEM images of recycled carbon black from all studied samples show the coalesced nanoparticles, sugar fabric, and porous media due to the desulfurization process. This paper’s outputs could primarily be applied for developing any pilot or industrial plant for tire recycling in Iran and economic analysis of investment return rate as well.